FACTORS INFLUENCING THE ART OF SCULPTURE IN CHINA’S LONGMEN GROTTOES: “RELIGIOUS COLORS, CULTURE, AND RELIEF SCULPTURE” (Applied History Journal of Merong Mahawangsa, 2025)
This paper examines the art of sculpture in China from the Northern and Southern Dynasties to the Tang Dynasty, focusing on the Longmen Grottoes located in Luoyang City, Henan Province. The study focuses on the religious colours and relief techniques of Longmen Grottoes sculpture, exploring the influence of Buddhism on the styling of Chinese royalty and the development of sculpture in later generations. By comparing the statues of the Longmen Grottoes of the Northern and Southern Dynasties and the Tang Dynasty, the sculptures are analysed in terms of their demeanour, colour, statue assemblage, and relief content. It is found that religious concepts have had a profound influence on the evolution of Chinese sculpture art at different historical stages. At the same time, with the change of times, religious ideas also influenced the development of sculpture technology. In addition, by analysing the typology and modelling mechanics of the representative sculptures of Buddha, Bodhisattva and Flying Sky in the Longmen Grottoes, the sculpture modelling is integrated with the Buddhist beliefs, classics and national culture of the time. Ultimately, the influence of religious culture on ancient Chinese sculpture art is explored to provide new perspectives for the establishment of a sculpture teaching and modelling system with local characteristics.